A Selective Review on Recent Development of Displacement-Based Laminated Plate Theories - Wanji, Chen; Zhen, Wu (Recent Patents on Mechanical Engineering, 2008)
This paper reviews the recent development of displacement-based theories for laminated composite plates as well as corresponding finite element models. Discussion focuses on the accuracy and efficiency of various theories, and the detailed expression of typical displacement theories used herein is also presented. To objectively assess these theories, Pagano's cylindrical bending problems are chosen for comparison of various theories. Numerical results show that the global-local theories are more suitable for prediction of transverse shear stresses directly from constitutive equations in comparison with other theories. However, the zig-zag theories satisfying the interlaminar continuity of transverse shear stresses are still unable to accurately predict transverse shear stresses directly from constitutive equations, in which in order to obtain satisfactory transverse shear stresses, 3D equilibrium equations have to be adopted. In addition, free vibrations and stability of soft-core sandwiches are also considered to further assess various displacementbased laminated plate theories. Numerical results show that the global displacement theories will encounter difficulties to accurately predict the dynamic and the buckling response of so special structures. However, the global-local theories satisfying the continuity of transverse shear stresses at interfaces are still suitable for the dynamic and the buckling problems of soft-core sandwiches. In addition, this paper also includes some information of recent patents on the processes for the fabrication of composite metal object as well as functionally graded materials, and the methods of making nanofibre yarns, ribbons and sheets et al.
Keywords: Displacement-based theories